The palace - Reich, Christopher, 1961- (Reich, Christopher, 1961- Simon Riske novel., 2020)
When a man to whom he owes his life reaches out from prison, international spy Simon Riske recruits a daring investigative reporter and a rogue Mossad agent to thwart an international conspiracy targeting major European cities.